Crazy without insanity. To the phenomenology of personal disorders - Shahverdyan, Gayane (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article is devoted to the phenomenology of personal disorders. It is shown that the main symptom of this pathology is selfishness and inability to empathy. An attempt has been made to explain this phenomenon from the point of view of thinking, which functions without the participation of experience and will.